Comparative study of trauma-related phenomena in subjects with pseudoseizures and subjects with epilepsy. - Fleisher, William; Staley, Douglas; Krawetz, Patricia (American Journal of Psychiatry, 2002)
Objective: The purpose of this study was to examine potential differences in measures of trauma-related phenomena between subjects with pseudoseizures and subjects with intractable epilepsy. Method: Thirty-one adult subjects with pseudoseizures and 32 subjects with intractable epilepsy (confirmed by video-EEG) were recruited from the epilepsy unit of a tertiary care hospital. Each participant completed the Impact of Event Scale, the Davidson Trauma Scale, the Mississippi Scale for Combat-Related Posttraumatic Stress Disorder (PTSD), the Dissociative Experience Scale, and the Pittsburgh Sleep Quality Index, as well as demographic, seizure history, and family functioning measures. Results: Subjects with pseudoseizures had significantly higher mean scores on the Davidson Trauma Scale, Mississippi Scale for Combat-Related PTSD, Impact of Event Scale, and Pittsburgh Sleep Quality Index than subjects with epilepsy. In addition, a significantly higher percentage of subjects with pseudoseizures had scores above the clinical cutoff level of 30 on the Dissociative Experience Scale. Conclusions: Subjects with pseudoseizures exhibited trauma-related profiles that differed significantly from those of epileptic comparison subjects and closely resembled those of individuals with a history of traumatic experiences. Interventions aimed at trauma-related issues may be beneficial for patients with pseudoseizures. Reprinted by permission of the publisher.